Analysis of Banking Stock Performance Before, During, and After the COVID-19 Pandemic on the Indonesia Stock Exchange (IDX) - Tompo, Cherilyn Cristine; Sidjaja, Derrick Nelson; Thenikusuma, Arnold; Maichal, Maichal (Universitas Muhammadiyah Yogyakarta, 2025)
This study analyzes the performance differences of Indonesia’s banking sector stocks, represented by the Infobank15 index, before, during, and after the COVID-19 pandemic. Using ANOVA and Post Hoc Testing, the study finds no significant differences in stock returns across these three periods despite the substantial economic disruption caused by the pandemic. Like other industries, the banking sector faced a downturn at the start of the pandemic but managed to recover. This finding underscores that the banking sector maintained stability across different periods due to the strong financial fundamentals, including consistent Non-Performing Loan (NPL) and Return on Assets (ROA) ratios throughout the pandemic. The government’s support, such as credit restructuring policies and digitalization of banking services, facilitated the sector’s adaptation to economic challenges, allowing for continued operations despite social restrictions. The study highlights that the banking sector’s ability to expand its digital services mitigated the crisis's immediate impacts and positioned it as an attractive option for investors seeking stability. This study offers insights for policymakers and adds to the literature on the banking sector’s resilience during global crises.